Pola Asuh Orang Tua Dalam Mendidik Anak Remaja Di Mts Negeri 11 Cirebon - Nurwakiah, Nurwakiah; Herawati, Endang Sribudi; Kholik, Abdul (Jurnal Eksplorasi Bimbingan dan Konseling, 2023)
Parenting is the treatment given to children in order to provide affection, protection, guidance, direction and education in everyday life and how parents behave in their relationships with their children. The task of parental obligations is to educate. In educating adolescents (13-16 years old) parents carry out different parenting patterns. The majority of parents at MTs Cirebon are busy working. This happened based on a case study at MTs Negeri 11 Cirebon. So it is necessary to conduct research with the aim of determining parenting patterns that have an impact on adolescent behavior. The research method uses a qualitative method with an interactive qualitative case study research type. The research subjects numbered 6 people consisting of 3 parents and 3 students (some of whom were in class IX B, IX C, and IX D) at MTs Negeri 11 Cirebon with a purposive sampling technique. The instruments used were interviews, observations and documentation. The results obtained, parenting patterns are influenced by the amount of working time, work, educational background and communication built with adolescents. This is what distinguishes parenting patterns in educating adolescents at MTs Negeri 11 Cirebon. So because of the differences in parenting patterns, it can shape the behavior of adolescents at MTs Negeri 11 Cirebon.